Intense proximity : an anthology of the near and the far - Enwezor, Okwui; Bouteloup, Mélanie; Karroun, Abdellah; Renard, Emilie; Staebler, Claire (Paris : Artlys, 2012)
Griaule, Marcel ; Lam, Wifredo ; Verger,Pierre ; Evans, Walker ; Lévi-Strauss, Claude ; Levitt, Helen ; Rouch, Jean ; Rama, Carol ; Kožarić, Ivan ; Brǎtescu, Geta ; et al.
La Triennale 2012, Palais de Tokyo and other Paris-based institutions, Paris, April 20 trough August 26-2012
boek